Solution: If 2log3 (base x) + log2 (base x) = 2 + log6 (base x), then x equals

If 2log3 (base x) + log2 (base x) = 2 + log6 (base x), then x equals. How to solve involving logarithmic functions?

If 2log3 (base x) + log2 (base x) = 2 + log6 (base x), then x equals

Problem Statement:

If 2log3 (base x) + log2 (base x) = 2 + log6 (base x), then x equals

Problem Answer:

x equals √3

Solution:

Post a Comment

Contact Form

Name

Email *

Message *

Powered by Blogger.
Javascript DisablePlease Enable Javascript To See All Widget